Britain's birds : an identification guide to the birds of Britain and Ireland - Hume, Rob; Still, Rob; Swash, Andy; Harrop, Hugh; Tipling, David (WildGuides., 2020)
"A bestselling guide since it was first published, Britain's Birds has quickly established itself as the go-to photographic identification guide to the birds of Great Britain and Ireland--the most comprehensive, up-to-date, practical and user-friendly book of its kind. Acclaimed by birdwatchers of all kinds, from the beginner to the most experienced, the guide has now been thoroughly revised and updated to make it even better than before. Combining the finest of identification guide content and presentation, this eagerly awaited second edition preserves the best of the first edition while covering twelve newly recorded species and offering a host of improvements that make identification easier. Provides comprehensive coverage of all the birds ever recorded in Britain and Ireland Describes and illustrates all plumages likely to be encountered Features more than 3,200 stunning photographs carefully selected to show the birds as you really see them Outlines simple steps to help you identify any bird you see Presents simple and accurate comparisons of similar and difficult species New features include: Coverage of 12 new species recorded since the first edition plus revisions to reflect the latest taxonomy Coverage of all subspecies Improved identification aids, including more than 400 new photos, enhanced photo annotations and many redesigned plates Fully revised species accounts, including the latest information on identification features, status, numbers, geographical range and date ranges for all plumages that may be seen during only part of the year" --